Structures and luminescent properties of lanthanide phosphonates - Mao, Jiang-Gao (Coordination chemistry reviews, 2007)
The crystal structures and luminescent properties of lanthanide phosphonates are reviewed. The structural elucidation for lanthanide phosphonates is difficult due to its low solubility and poor crystallinity. To overcome these problems, two types of synthetic techniques were applied: attaching various functional groups or introducing a second metal linker. By attaching various types of functional groups to the phosphonate ligand, lanthanide phosphonates with 0D, 1D, 2D and 3D structures have been isolated. Using the acidic metal linker such as oxalate usually leads to compounds with a complicated 3D network structure whereas a basic second metal linker such as phen helps the formation of compounds containing the polynuclear clusters. Phosphonic acids are versatile ligands that can adopt a number of coordination modes depending on the cation size, temperature and the pH value of the reaction media. The luminescence properties of some lanthanide phosphonates are also discussed.